2000
DOI: 10.1073/pnas.200371497
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive regulation of intestinal lysine metabolism

Abstract: The metabolism of dietary essential amino acids by the gut has a direct effect on their systemic availability and potentially limits growth. We demonstrate that, in neonatal pigs bearing portal and arterial catheters and fed a diet containing 23% protein [high protein (HP) diet], more than half the intake of essential amino acids is metabolized by the portal-drained viscera (PDV). Intraduodenal or i.v. infusions of [U-13 C]-lysine were used to measure the appearance across and the use of the tracer by the PDV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 36 publications
7
102
1
Order By: Relevance
“…Oxidation of essential amino acids by the PDV has been reported in studies with young animals (i.e., lysine, leucine) (43,44,50,51). Phenylalanine oxidation by the PDV accounted for nearly 40% of whole body phenylalanine oxidation in the current study.…”
Section: Discussionsupporting
confidence: 68%
“…Oxidation of essential amino acids by the PDV has been reported in studies with young animals (i.e., lysine, leucine) (43,44,50,51). Phenylalanine oxidation by the PDV accounted for nearly 40% of whole body phenylalanine oxidation in the current study.…”
Section: Discussionsupporting
confidence: 68%
“…Our previous studies have shown that GIT extensively metabolize dietary indispensable amino acids, namely lysine, threonine, and leucine (24 -26). In the case of methionine, our studies and those of others suggest that substantial metabolism and even oxidation of dietary methionine occurs in the gut (26,27). However, the extent of transmethylation and transsulfuration in the GIT and its relative contribution to whole-body methionine metabolism has not been established.…”
mentioning
confidence: 50%
“…Methionine and cystine contents were 0.52% and 0.61%, respectively, providing a daily intake of 0.25 g methionine/kg and 0.31 g of cystine/kg. At 20 days of age, the piglets (n ϭ 16) were surgically implanted with catheters as described (26,41). One week after surgery, each piglet received ID and IV tracer infusions on two different days in a randomized, cross-over design with at least one day between the ID and IV infusions.…”
Section: Methodsmentioning
confidence: 99%
“…From 08.00 to 14.00 hours, pigs were offered meals at hourly intervals, and the meal was the equivalent of one twenty-fourth of the daily intake (45 g/kg BW). Immediately after the first meal, piglets received a constant infusion of [1-13 C]methionine, suspended in water via the gastric catheter at a rate of about 0·25 ml/min to provide [1][2][3][4][5][6][7][8][9][10][11][12][13] C]methionine at 7·0 mmol/kg BW per h. After the tracer infusion was started, the piglets continued to receive hourly meals. Arterial and portal blood samples were taken at hourly intervals until 6 h of tracer infusion, and all the blood samples were immediately placed on ice.…”
Section: Infusion Protocol and Blood Collectionmentioning
confidence: 99%